2021
DOI: 10.3390/ijerph182111130
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviour Changes during the COVID-19 Pandemic: A Systematic Review of Longitudinal Studies

Abstract: Eating behaviour is a complex construct that is liable to be modified by external factors. Due to the outbreak of coronavirus disease 2019 (COVID-19), many restrictive measures were carried out with the aim of reducing the impact of this disease. As a result, lifestyles were disrupted, which could affect eating behaviours. The aim of this systematic review of longitudinal studies was to assess changes in eating behaviour during the COVID-19 pandemic by establishing a comparison of eating behaviours before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
119
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 57 publications
10
119
1
2
Order By: Relevance
“…Consumption of meat, fruits, and eggs among households has decreased during the COVID-19 pandemic. This finding aligns with several recent studies that reported rapid changes in diets and food consumption habits during the COVID-19 pandemic ( 46 , 48 , 49 ). During the COVID outbreak, due to the increase in the price of animal protein sources, the access of low-income decile groups to these items has decreased ( 50 ).…”
Section: Discussionsupporting
confidence: 93%
“…Consumption of meat, fruits, and eggs among households has decreased during the COVID-19 pandemic. This finding aligns with several recent studies that reported rapid changes in diets and food consumption habits during the COVID-19 pandemic ( 46 , 48 , 49 ). During the COVID outbreak, due to the increase in the price of animal protein sources, the access of low-income decile groups to these items has decreased ( 50 ).…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to the limitation of social gatherings, as noted by Rehm et al (2020) [57]. The 2021 review shows the overall increase in alcohol consumption during the COVID-19 pandemic [58]. On the other hand, no changes in coffee consumption were observed, whereas a statistically significant increase in tea consumption was noted, which is in line with the review by Castellana et al (2021).…”
Section: Discussionsupporting
confidence: 58%
“…Other researchers obtained different results [45,49,54]. An increase in the consumption of sweets was also noted in the review by Gonzalez-Monroy et al (2021) [58]. Their increased consumption could be associated with an increase in stress accompanying the pandemic [60].…”
Section: Discussionmentioning
confidence: 89%
“…How long routine changes are sustained after lockdown is yet to be fully evaluated; however, at the time of the present study, those with positive behaviour changes appeared conscious about the need to maintain good habits. Changes in physical activity [ 75 ], diet [ 76 ], substance use and other health behaviours [ 77 , 78 ] are highlighted in the international literature, often suggesting negative implications because of distancing and COVID-19. Other literature suggests that home-based activities such as exercise, yoga, and relaxation [ 79 , 80 ] and access to green spaces [ 35 , 81 ] can improve wellbeing during the COVID-19 pandemic, although perhaps only for more mobile members of the population.…”
Section: Discussionmentioning
confidence: 99%